PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN - Faridhatun Nafi’ah; Adelia Yunita Setiyadi; Tara Umi Nur Wakhidatun; Arif Setiawan; Rauly Sijabat (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of compensation on employee behavior within organizations. Compensation is an important factor influencing motivation, job satisfaction, and employee loyalty. This research uses a qualitative descriptive approach with a literature study method to examine the relationship between compensation and employee work behavior. The results show that a fair and competitive compensation system has a positive impact on productive, participatory, and loyal work behavior. Conversely, unfair compensation can lead to negative behaviors such as decreased performance, absenteeism, and turnover. These findings indicate that the role of management in designing a transparent and fair compensation system is crucial in shaping a healthy organizational work environment.